Hubungan Kejadian Penyakit Pada Ovarium terhadap Terjadinya Infertilitas di Rumah Sakit Umum Daerah Haji Makassar tahun 2015 - Hatijar, Hatijar (Journal of Islamic Medicine, 2019)
Abnormalities / diseases of the ovary are manifestations of growth deviations and organ formation. Abnormalities / diseases of the ovary are closely related to women who have low fertility or experience infertility. Objective: to determine the relationship of Ovarian Disease Occurrence to the occurrence of Infertility in Haji Makassar General Hospital in 2015. Research Methods: This research is a quantitative type of research with descriptive analytic research type. Subjects were mothers who suffered from ovarian disease who were treated in the Gynecological Room of the Makassar Haji General Hospital as many as 52 people were treated in the obstetric room. The research sample was taken with purposive sampling technique totaling 37 respondents. Data were analyzed by univariate and bivariate using Chi-Square statistical test with a significance value of P-value 95% (p = 0.05). Result: there is a relationship between disease in the ovary and infertility (p = 0,000). Conclusion: there is a relationship between disease in the ovary and infertility.